2010
DOI: 10.1097/acm.0b013e3181d2cdf1
|View full text |Cite
|
Sign up to set email alerts
|

Core Clerkship Directors: Their Current Resources and the Rewards of the Role

Abstract: The resources and rewards of the clerkship director role were similar across disciplines. Expectations of clerkship directors were considerable, including responsibility for clinical material and the learning environment. Resources for many fall short of those stated in the ACE guidelines, particularly regarding support staff. However, the findings indicate that the clerkship director role can have benefits for academic advancement and strongly enhances career satisfaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 20 publications
2
17
0
Order By: Relevance
“…This study used the data that was previously reported by Coates in 2005 5. At the time of the Margo study, EM CDs were younger, more likely to be junior faculty at the clinical instructor or assistant professor rank and had less protected time afforded to support their role as CD when compared to their counterparts in other specialties 11,12. Little has changed over the 6 years since the Coates study.…”
Section: Discussionmentioning
confidence: 99%
“…This study used the data that was previously reported by Coates in 2005 5. At the time of the Margo study, EM CDs were younger, more likely to be junior faculty at the clinical instructor or assistant professor rank and had less protected time afforded to support their role as CD when compared to their counterparts in other specialties 11,12. Little has changed over the 6 years since the Coates study.…”
Section: Discussionmentioning
confidence: 99%
“…In a survey of clinical directors representing several different medical specialty areas, there was similarity across fields with demographics and academic productivity, despite variability in the daily clinical routines and clerkship activities (Ephgrave et al, 2010). Strickler's (1991) survey of physical therapy academic clinical coordinators of education found they spend 24% of their time in the classroom teaching, 52% on clinical education activities, and 24% on clinical practice, scholarship, and service.…”
Section: Tasks Of the Rolementioning
confidence: 98%
“…The high response rate on both surveys (approximately 75%), which is a strength of this study, helps ensure the validity of the data. While other surveys 2 have included neurology CDs as part of a larger population of CDs, this is the first report specific to US neurology CDs and the first to look at these trends over time. The intentional inclusion of similar questions in both surveys allows evaluation of trends over time.…”
Section: Assessment Methodsmentioning
confidence: 99%
“…Similar results have been seen in other surveys of CDs. 2,8 We hope that the data presented in this report will be helpful for CDs, program directors, department chairs, medical school deans, and other educators who have an interest in teaching the next generation of physicians by helping to establish national benchmarks for neurology clerkships. We hope this report will stimulate discussion about the resources and support needed for clinical education in general and neurology education in particular.…”
Section: Assessment Methodsmentioning
confidence: 99%
See 1 more Smart Citation